Mycotoxic effects of entomopathogenic fungi of fall armyworm (Spodoptera frugiperda J.E. Smith) on poultry feed safety - Silipiwe, Sharai; Muriithi, Alice Nakhumicha; Ojiewo, Christopher Ochieng (BioMed Central, 2024)
This study was carried out to analyze mycotoxins of entomopathogenic fungi of fall armyworm (Spodoptera frugiperda J.E. Smith) and poultry feed safety. An experiment was set up to assess the types of mycotoxins produced by entomopathogenic fungal parasite of fall armyworm larvae and their subsequent effect on the safety of the larvae as a feed ingredient. Molecular characterization was done to estimate the diversity of entomopathogenic fungi on fall armyworm larvae specimens from the treatment plots. Sequenced data was analyzed and processed using Molecular Evolutionary Genetic Analysis 6.0 software. The results showed relative diversity of fall armyworm larvae with 11 species isolated belonging to Aspergillus, Penicillium, Fusarium, Trichoderma, Bipolaris and Irpex genus. Some of these are potential mycotoxin producing fungi. Although isolated fungi potentially produce Ochratoxin, Fumonisin, Zearalenone and Trichothecene mycotoxins, only aflatoxins were analyzed in this study. About 3.98 mu g /kg of aflatoxin was observed using the ELISA total assay which is within the threshold toxicity levels set in Kenya for feed of about 20 mu g /kg. While this is under the threshold set by Kenya, it is still enough to cause concern as the cumulative exposure of even low doses can have impacts. This study therefore concludes that, Spodoptera frugiperda can be potentially contaminated with aflatoxins and when formulating poultry diets, there is need to monitor production so that the quality is not compromised and feed safety is ensured. Further studies are recommended to determine how much produced aflatoxins are then transferred into the poultry products such as eggs and meat.